Collaborating to Compete: Blood Profiling Atlas in Cancer (BloodPAC) Consortium. Issue 5 (12th April 2017) - Grossman, RL; Abel, B; Angiuoli, S; Barrett, JC; Bassett, D; Bramlett, K; Blumenthal, GM; Carlsson, A; Cortese, R; DiGiovanna, J; Davis‐Dusenbery, B; Dittamore, R; et al.
Abstract : The cancer community understands the value of blood profiling measurements in assessing and monitoring cancer. We describe an effort among academic, government, biotechnology, diagnostic, and pharmaceutical companies called the Blood Profiling Atlas in Cancer (BloodPAC) Project. BloodPAC will aggregate, make freely available, and harmonize for further analyses, raw datasets, relevant associated clinical data (e.g., clinical diagnosis, treatment history, and outcomes), and sample preparation and handling protocols to accelerate the development of blood profiling assays.